The Use of Scarce Resources in Telecommunications: The Case of the Radio Spectrum and Numbering - Zegarra Valdivia, Diego (2005)
This article analyses the legal aspects related to the use of limited resources in the telecommunications sector, with a particular focus on radio spectrum and numbering. For this reason, various aspects related to the relevance of the radio spectrum are evaluated, including its demanial nature, the administrative authorization for its use, and its regulation. It also discusses crucial numbering issues, such as the Fundamental Technical Numbering Plan (PTFN), the management and supervision of this resource, the procedure for its allocation, the rights and obligations of numbering holders, and number portability. In this context, it is important to point towards a legal framework that guarantees an efficient and rational use of these resources by the sectoral administration, given their scarcity and the growing demand for services that depend on them.